Modeling of chloride leaching at Quezon City Controlled Dumping Facility (QCCDF), the Philippines - Chea, Kimleak (College of Engineering, University of the Philippines Diliman, 2014)
Quezon City Controlled Dumping Facility (OCCDE),otherwise known as the Payatas dump side, the oldest and largest among the existing dump sites in the Philippines.Impacts of contaminants generated from QCCDF are main challenge in conserving groundwater quality in the aquifier beneath and nearby QCCDF. Groundwater quality monitoring and modeling are essential tools in determining the current status and for the future prediction of groundwater quality band transport of contaminants.In response to this emerging issue in the study area,groundwater and leachate samples were collected from fifteen(15)wells and four(4)leachate control stations in QCCDF and are being monitored for chloride content for seven(7)times from April 2014 to August 2014.Groundwater flow simulation was conducted for the period of 1988 to 2014 in transient condition.Precipitation, recharge rates are the main forcing factors in the transport chloride.Result showed that pH (6.1) to 7.2),turbidity(<5NTU),conductivity 0.4-3.5 mS/cm)chloride(<250ppm),nitrate(<10ppm),and sulphate(<250ppm) conformed with water quality standards in all wells except for the turbidity at three wells and nitrate in one well. Total dissolved solids (0.58-2.16 g/l) are shown to be above the water quality standard limit of 0.5 g/l except in one well.Heavy metal analysis showed that copper (1.27-3.62ppm) in all monitoring well are above the standard limit of 1ppm, except v4 where observed Cu are below the standard limit of 1ppm, except for 4 wells where observed Cu are below the standard limit. However, observed values for zinc in well are below the standard.In Leachate samples,turbidity, total dissolved solid, chloride, sulphate, zinc and copper show remarkably high values.Further,value of total dissolved solid,turbidity,conductivity,and chloride concentration change with season (april and August values).Pearson correlation coefficient shows that chloride has strong positive correlation with conductivity (r=0.89) and total dissolved solid(r=0.88) in groundwater wells and temperature (r=0.9), conductivity (r=0.99), turbidity (r=0.94)and total dissolved solid (r=99) at leachate control stations.Groundwater Modeling System-FEMWATER, a three dimensional finite element computer model, was used to simulate groundwater flow and chloride transport. The hydraulic conductivity of garbage,sandy clay,conglomerate,mudstone,and sandstone are 15.98 m/day,0.017 m/day, 0.56m/day, 0.069m/day, and 0.48m/day, respectively.The most sensitive parameter to groundwater flow modeling is the recharge rate value from rainfall and leaching rate at the dumpsite. In the steady state flow condition, the calibrate values of recharge from rainfall and from dumpsite are 492.02 mm/year and 1752mm/year,respectively,providing the smallest value for RMSE (=1.40 m)and Pbias (=1.17%).In transient flow condition, the rate from rainfall and dumpsite are iput as transient value.In a scenario analysis,one scenario at varied inputs of calibrated parameters(dispersivities,recharge rate),provides the best simulation with smallest value for RMSE (=1.91 m )and Pbias(=1.09%).